Whole mount multiplexed visualization of DNA, mRNA, and protein in plant-parasitic nematodes - Alexis L. Sperling; Sebastian Eves-van den Akker (Plant Methods)
Abstract Background Plant-parasitic nematodes compromise the agriculture of a wide variety of the most common crops worldwide. Obtaining information on the fundamental biology of these organisms and how they infect the plant has been restricted by the ability to visualize intact nematodes using small molecule stains, antibodies, or in situ hybridization. Consequently, there is limited information available about the internal composition of the nematodes or the biology of the effector molecules they use to reprogram their host plant. Results We present the Sperling prep - a whole mount method for nematode preparation that enables staining with small molecules, antibodies, or in situ hybridization chain reaction. This method does not require specialized apparatus and utilizes typical laboratory equipment and materials. By dissociating the strong cuticle and interior muscle layers, we enabled entry of the small molecule stains into the tissue. After permeabilization, small molecule stains can be used to visualize the nuclei with the DNA stain DAPI and the internal structures of the digestive tract and longitudinal musculature with the filamentous actin stain phalloidin. The permeabilization even allows entry of larger antibodies, albeit with lower efficiency. Finally, this method works exceptionally well with in situ HCR. Using this method, we have visualized effector transcripts specific to the dorsal gland and the subventral grand of the sugar beet cyst nematode, Heterodera schachtii, multiplexed in the same nematode. Conclusion We were able to visualize the internal structures of the nematode as well as key effector transcripts that are used during plant infection and parasitism. Therefore, this method provides an important toolkit for studying the biology of plant-parasitic nematodes.